Shaping an Identity: Junior-Faculty Orientation in a Year-Long Seminar - Nelson Javier Nunez Rodriguez; Ernest Ialongo; Jacqueline Disanto; Antonios Varelas; Cynthia Jones; Sarah Brennan (Academic Chairpersons Conference Proceedings, 2016)
This one-year seminar prepares new faculty to meet institutional expectations in the areas of scholarship, teaching, and service in a community college. In doing so, the Center for Teaching and Learning harmonizes new faculty with departmental and institutional needs while fostering a safe environment for faculty acclimation.
Keywords: New-faculty; orientation; service; portfolio; development